Discovery and prioritization of variants and genes for kidney function in >1.2 million individuals - Kira J. Stanzick (Nature Portfolio, 2021)
Identifying causal variants and genes in genome-wide association studies remains a challenge, an issue that is ameliorated with larger sample sizes. Here the authors meta-analyze kidney function genome-wide association studies to identify new loci and fine-map loci to home in on variants and genes involved in kidney function.